Perbaikan Proses Pengeringan Kakao di Desa Sungai Langka Kecamatan Gedung Tataan Kabupaten Pesawaran - Warji, Warji; Tamrin, Tamrin (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2017)
Abstract — Indonesian cocoa production is significantly increasing, but the resulting quality is generally low and varied, especially those produced by smallholders. The low quality because of weak implementation of a cocoa processing technology, in particular the fermentation and drying of cocoa. Cocoa farmers in the village of Sungai Langka, Gedong Tataan, Pesawaran District, Lampung Province generally cultivate cocoa without fermentation process, they find it more practical and easier to peel their crops without fermentation. Cocoa beans stripping results directly in the sun on a concrete floor or paved with plastic tarps for a day or half a day later sold to traders. In fact, there are farmers who peeling cocoa in the morning and during the day has been sold to collectors. Likewise in traders, cocoa which has been purchased with a degree of dryness varies directly collected and dried again on a drying floor or plastic sheeting. When demand is high or the rainy season, new traders use a dryer. One of the traders in the village of Sungai Langka, Gedong Tataan, Pesawaran District is Mr. Arkan, where the technology used dryer Mr. Arkan is still very simple. Dryer used is the type of tub with a capacity of about 100 kg of cocoa beans per process with firewood fuel. The drying process directly, smoke and hot combustion products mixed into one and the cocoa beans are dried so that the cocoa beans drying results smelled of smoke. Both of the above conditions (absence of fermentation and drying process unfavorable) results in a lower quality of cocoa which is in turn the price is relatively low. Therefore, there needs to be a cocoa processing technology applications at the farm level fermentation and drying technologies, in particular at the level of the collector to be able to produce high quality cocoa in a sustainable manner. Therefore Proposer team intends to apply the method of fermentation of good and apply the hybrid type dryers on farmer groups and traders of cocoa in Village of Sungai Langka, Gedong Gedong Tataan, Pesawaran District. Drier hybrid that will be applied to biomass-fired, gas or electricity in addition to its main source of sunlight, so the cocoa drying with a dryer hybrid type can be done throughout the season and the quality is good. Keywords — Cocoa, fermentation, drying, dryers hybrid type